Efeitos da hemorragia subaracnóidea sobre a motilidade gastrintestinal em ratos - Mendes, Tiago Santos (2014)
Subarachnoid hemorrhage (SAH) can arise from various types of damage to the central nervous system. The HSA can increase intracranial pressure (ICP) to levels high morbidity. In addition to neurological and cardiovascular symptoms, well described in the literature; gastrointestinal symptoms such as nausea, vomiting and gastroenteritis are common but little studied. The delay gastric emptying (GE) is one of the physiological changes found in patients with intracranial hypertension (ICH). This disorder reduces therapeutic responses with a view to reducing the absorption of nutrients and drugs, and lead to lung aspiration, which can lead to death. We evaluated the effect of HSA on gastrointestinal motility disorders (Gastric Emptying - EG; Intestinal Transit – IT or Gastric Compliance - CG), hemodynamic parameters (Mean Arterial Pressure - MAP, Heart Rate - HR) and the PIC. As well as neurohumoral mechanisms related to these changes. We used Wistar rats (300 - 350g, N=113) under the auspices COBEA (CEUA/UFC- Protocol 41/13). After anesthesia (Ketamine/Xylazine 20-10mg/Kg-IP), the animals were restrained by stereotactic aparatus being injected 0.1, 0.2 or 0.3 ml in the cisterna magna (autologous blood - HSA group or Liquor simile - Control group). At the time of induction of HSA, the animals were subjected to cannulation of the lateral ventricles for measurement of ICP and rigth femoral vessels in order to obtain the hemodynamic data. After 72h of induction, and fasted (24h) animals with oral rehydration solution ad libitum, proceeded studies EG, IT and CG. To determine the rate of GE a test meal (1ml/100g - phenol red - 0.5 mg/ml in 5 % glucose) was administered by gavage. The IT was already determined on direct administration of the meal into the duodenum through previously implanted cannula. Since the CG was evaluated using a barostat system at 4, 8 and 12 cm of gastric pressure distension. The MAP, HR and ICP were measured when assessing gastrointestinal motility. Data, mean ± SEM, were analyzed by the "t" Student test (p<0.05). The HSA delayed gastric emptying (38.90 ± 2.73 vs 47.00 ± 0.72 %; 52.85 ± 5.14 vs 31.12 ± 2.0 % and 22.89 ± 4.46 vs 46,24 ± 3.56 % ) and increased the ICP (3.33 ± 0.47 vs 16.10 ± 0.47 cmH2O; 7.68 ± 0.650 vs 30.86±0.82 cmH2O and 17.50 ± 1.29 vs 37.90 ± 1.38 cmH2O ) in different volumes of blood, either 0.1, 0.2 or 0.3 ml, respectively, when compared to control. The HSA also promoted delay in IT and GC, increased BP and decreased HR. The subdiaphragmatic vagotomy, the esplancnotomia and pretreatment with guanethidine reversed the effect of HSA on changes in EG. The results suggest that the SAH arising gastrointestinal diseases reflect a pattern of secondary gut dysmotility, showing a strong correlation with the values of ICP.